2021
DOI: 10.1039/d1na00142f
|View full text |Cite
|
Sign up to set email alerts
|

Size-tunable and stable cesium lead-bromide perovskite nanocubes with near-unity photoluminescence quantum yield

Abstract: Stable cesium lead bromide perovskite nanocrystals (NCs) showing near-unity photoluminescence quantum yield (PLQY), narrow emission profile, and tunable fluorescence peak in the green region can be considered the ideal class...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…32 The dispersion of the chosen lead precursor (PbBr 2 ) in toluene was accomplished by the presence of an equimolar amount of (n-Hept) 4 NBr salt, promoting the formation of soluble intermediates. 33 The modulation of the halide component (to regard the blue region in emission for the corresponding NCs, vide inf ra) was subsequently performed by introducing the suitable quantity of dimethyldioctadecylammonium chloride (DODC) in the reaction mixture (PbBr 2 /DODC = 5:1 mol/mol) before the cesium injection, as schematized in Figure 1. Notwithstanding the structural analogy of the two organic cations used in this synthetic sequence, we observed that the presence of (n-Hept) 4 NBr in the first step was indispensable for warranting the complete dissolution of the lead precursor, which does not occur by utilizing only DODC as a surfactant even at higher concentrations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 The dispersion of the chosen lead precursor (PbBr 2 ) in toluene was accomplished by the presence of an equimolar amount of (n-Hept) 4 NBr salt, promoting the formation of soluble intermediates. 33 The modulation of the halide component (to regard the blue region in emission for the corresponding NCs, vide inf ra) was subsequently performed by introducing the suitable quantity of dimethyldioctadecylammonium chloride (DODC) in the reaction mixture (PbBr 2 /DODC = 5:1 mol/mol) before the cesium injection, as schematized in Figure 1. Notwithstanding the structural analogy of the two organic cations used in this synthetic sequence, we observed that the presence of (n-Hept) 4 NBr in the first step was indispensable for warranting the complete dissolution of the lead precursor, which does not occur by utilizing only DODC as a surfactant even at higher concentrations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This route allowed to bypass the conventional dissolution step of the ionic precursors of LHP NCs requiring high temperatures or aggressive polar solvents . The dispersion of the chosen lead precursor (PbBr 2 ) in toluene was accomplished by the presence of an equimolar amount of ( n -Hept) 4 NBr salt, promoting the formation of soluble intermediates . The modulation of the halide component (to regard the blue region in emission for the corresponding NCs, vide infra ) was subsequently performed by introducing the suitable quantity of dimethyldioctadecylammonium chloride (DODC) in the reaction mixture (PbBr 2 /DODC = 5:1 mol/mol) before the cesium injection, as schematized in Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Our results of quantum-confined blue emission from perovskite NCs provide an alternative to mixed halide perovskites and, together with its enhanced stability, could be useful in the realization of blue perovskite LEDs. The PLQY for the green emitting NCs is also high, though rather comparable to other synthesis method [39][40][41]. Yet, the advantage of the mechanochemical synthesis method is the high material yield, providing grams of NCs in a one-pot synthesis in just 1 h.…”
Section: Resultsmentioning
confidence: 72%
“…Despite significant progress in the thickness‐controlled synthesis with monolayer precision, pristine perovskite NPls usually suffer from low PLQY and colloidal instability as compared with nanocubes. [ 9,14,72,105 ] Although near‐unity PLQY is easily achievable for perovskite nanocubes under optimized conditions, [ 118–120 ] it has been often observed that the PL efficiency decreases for NPLs with decreasing thickness and therefore wide bandgaps. [ 28,29,71 ] In principle, 2D NPls are expected to exhibit high PLQY due to the enhanced radiative recombination caused by the confinement of charge carriers.…”
Section: Synthesis Of Nanoplateletsmentioning
confidence: 99%